Diagnosis and management of acute appendicitis in 21 pediatric hematology and oncology patients at a tertiary care cancer center - Hannah von Mersi (Nature Portfolio, 2021)
Abstract Acute appendicitis is a rare gastrointestinal complication of anti-cancer chemotherapy and hematopoietic stem cell transplantation. Among a cohort of 2341 hemato-oncologic patients at a pediatric tertiary care cancer center, we identified 21 patients (0.9%) with 23 episodes of acute appendicitis, based on pathological imaging of the appendix and clinical findings. Median age at diagnosis was 10.21 years. Types of underlying disease included acute leukemias (n = 15), solid tumors (n = 4), and aplastic anemia (n = 2). Clinical symptoms seen in > 1 case were recorded for all 23 episodes as follows: abdominal pain, n = 22; abdominal tenderness, n = 4; fever, n = 7; nausea, n = 2; emesis; n = 2; diarrhea, n = 5; and constipation, n = 2. Median leukocyte count at diagnosis was 0.5 × 109/L, with a median of 0.1 × 109/L for the absolute neutrophil count (ANC). All patients received broad-spectrum antibiotics and 18/23 (78%) patients underwent uneventful appendectomy after a median of 5 days and with a median ANC of 0.7 × 109/L. Median duration until continuation of chemotherapy was 17 days for the 20 cases of appendicitis occurring during the patients’ disease course. Overall, 5/21 (19%) patients died including one related to the appendicitis itself which progressed to a typhlitis and was due to a fungal infection. The other fatalities were transplant- (n = 2) and leukemia-related (n = 2). Acute appendicitis is a rare and usually not life-threatening event in pediatric hemato-oncologic patients, which, if managed by prompt administration of broad-spectrum antibiotics (and antimycotics), can be safely followed by an elective (delayed) appendectomy, even before complete recovery of the neutrophils is achieved.